2005
DOI: 10.1007/s00429-005-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid and pituitary gland development from hatching through metamorphosis of a teleost flatfish, the Atlantic halibut

Abstract: Fish larval development, not least the spectacular process of flatfish metamorphosis, appears to be under complex endocrine control, many aspects of which are still not fully elucidated. In order to obtain data on the functional development of two major endocrine glands, the pituitary and the thyroid, during flatfish metamorphosis, histology, immunohistochemistry and in situ hybridization techniques were applied on larvae of the Atlantic halibut (Hippoglossus hippoglossus), a large, marine flatfish species, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 83 publications
6
67
0
1
Order By: Relevance
“…In fish, the thyroid is not macroscopically recognized but present scattered thyroid follicles (Gorbman et al 1983). Anatomically the thyroid tissue in teleost fishes is composed by several follicles, which can be found near the ventral aorta and to the arterial bulb (Santamaría et al 2004, Delgado et al 2006 and in the insertion of the branchial arch (Einarsdóttir et al 2006), as was also observed for cobia in the present study.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In fish, the thyroid is not macroscopically recognized but present scattered thyroid follicles (Gorbman et al 1983). Anatomically the thyroid tissue in teleost fishes is composed by several follicles, which can be found near the ventral aorta and to the arterial bulb (Santamaría et al 2004, Delgado et al 2006 and in the insertion of the branchial arch (Einarsdóttir et al 2006), as was also observed for cobia in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…The thyroid follicle appearance during the transition of the endogenous feeding to the exogenous is essential for the synthesis of its own THs, because during the embryonary development and during the yolk sac absorption the THs are from maternal origin (Tagawa and Hirano 1987, 1990, Tanaka et al 1995, Yamano 2005, Delgado et al 2006. It was observed by Einarsdóttir et al (2006) in Hippoglossus hippoglossus that with larval development, the number of thyroid follicles increase and the colloid volume decreases. The authors attributed this phenomenon as indicative of the thyroid tissue activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Then, the upper phase was removed, lyophilised, reconstituted in assay buffer (0.01·mol·l -1 PBS, pH·7.6) and assayed. Assays for both T3 and T4 were highly specific and reproducible and were performed as previously described (Einarsdóttir et al, 2006) under equilibrium conditions, using T2777 anti-T3 (<0.01% cross reactivity with T4; SigmaAldrich) and T2652 anti-T4 polyclonal sera (~3% cross reactivity with T3; Sigma-Aldrich). Results are presented as means ± s.e.m.…”
Section: Th Extraction and Radioimmunoassaymentioning
confidence: 99%
“…The lack of colloidal mass inside thyroid follicles indicates that the colloidal mass was in use or, in another word, indicates the ongoing activity of thyroid follicles [20]. The colloid inside follicles contains thyroid hormone.…”
Section: Discussionmentioning
confidence: 99%